2008
DOI: 10.1016/j.neuron.2008.09.041
|View full text |Cite
|
Sign up to set email alerts
|

Diverse and Temporally Precise Kinetic Feature Selectivity in the VPm Thalamic Nucleus

Abstract: The thalamo-cortical pathway is the crucial sensory gateway into the cerebral cortex. We aimed to determine the nature of the tactile information encoded by neurons in the whisker somatosensory relay nucleus (VPm). We wanted to distinguish whether VPm neurons encode similar stimulus features, acting as a single information channel, or encode diverse features. We recorded responses to whisker deflections that thoroughly explored the space of temporal stimulus variables and identified features to which neurons w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
128
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(140 citation statements)
references
References 55 publications
11
128
1
Order By: Relevance
“…This is supported by intracellular recording which showed that as direction diverges from the preferred direction vibrissa-evoked EPSPs in barrel neurons decrease in amplitude and increase in onset latency (Wilent and Contreras, 2005). Petersen et al, 2008). Yet, the use of a spike latency code requires a reference signal for decoding its meaning.…”
Section: Rate Code Versus Latency Codementioning
confidence: 76%
See 1 more Smart Citation
“…This is supported by intracellular recording which showed that as direction diverges from the preferred direction vibrissa-evoked EPSPs in barrel neurons decrease in amplitude and increase in onset latency (Wilent and Contreras, 2005). Petersen et al, 2008). Yet, the use of a spike latency code requires a reference signal for decoding its meaning.…”
Section: Rate Code Versus Latency Codementioning
confidence: 76%
“…However, recent studies indicated that precise spike timing in ventral posterior medial nucleus (VPM) can also convey a remarkable amount of information (Montemurro et al, 2007;Petersen et al, 2008). We thus used the mean number of spikes per deflection and first-spike latency to build polar plots of angular preference.…”
Section: Methodsmentioning
confidence: 99%
“…This accounts for the robustness of the spike response across a large range of voltages, and this newly described intrinsic property impacts on the whole transfer function of the TC neurons that become quasi-invariant to significant membrane potential changes in the region between Ϫ55 and Ϫ72 mV. Such voltage invariance of EPSPs spike probability may be particularly important in the somatosensory system where the information transfer is believed to rely on a precise spike timing code both at the level of the trigeminal complex (Jones et al, 2004) and the ventroposterior medial nucleus of the thalamus (Montemurro et al, 2007;Petersen et al, 2008). Similarly in the visual system, such a voltage invariance may support the experimentally observed "relative precision" of the temporal structure in the thalamic neuronal response, which is necessary to represent accurately the more slowly changing visual world (Butts et al, 2007;Desbordes et al, 2008).…”
Section: Voltage Invariance Of the Spike Responsementioning
confidence: 97%
“…In their simplest form, LN models consist of a single linear filter and a static nonlinearity. As the kind of representation found at the level of ascending neurons suggests more complex transformations, we used an extension of the one-filter LN models that allowed us to describe multidimensional computations-spike-triggered covariance analysis (STC; Rust et al, 2005;Fairhall et al, 2006;Petersen et al, 2008;Fox et al, 2010).…”
Section: Introductionmentioning
confidence: 99%